Madagascar [videorecording (DVD)] : the land where evolution ran wild - Attenborough, David, 1926- (BBC/Warner Home Video, 2011)
For 65 million years, Madagascar was lost to the world, isolated, undiscovered, and untouched by humans. Left to its own devices it became a hotbed of evolution, resulting in the greatest concentration of unique creatures anywhere on the planet. More than 80% of Madagascar's animals and plants are found nowhere else on Earth. Recognized as one of the world's most important biodiversity hotspots.